Calycosin induces autophagy and apoptosis via Sestrin2/AMPK/mTOR in human papillary thyroid cancer cells - Qu, Na; Qu, Junsheng; Huang, Na; Zhang, Kexin; Ye, Tongtong; Shi, Junfeng; Chen, Bing; Kan, Chengxia; Zhang, Jingwen; Han, Fang; Hou, Ningning; Sun, Xiaodong; et al. (Frontiers in Pharmacology, 2022)
Calycosin, one of small molecules derived from astragalus, has anti-tumor effects in various tumors. However, the eﬀects of calycosin on papillary thyroid cancer (PTC) remain unclear. This study aimed to explore the anti-tumor ability of calycosin on human PTC and its potential mechanisms. The B-CPAP cells were treated with calycosin, then cell proliferation, apoptosis and invasiveness were measured by CCK8 assay, ﬂow cytometry, wound healing and transwell invasion assay, respectively. The cells were also performed by whole transcriptome microarray bioinformatics analysis. Apoptosis and autophagy-related markers or proteins were measured by qRT-PCR or western blot. Sestrin2-mediated AMPK/mTOR pathways were determined by western blot. We found that calycosin inhibited migration and invasion of B-CPAP cells and induced apoptosis (Bax/Bcl-2) and autophagy (LC3II/I, Beclin1) of B-CPAP cells. Differential expressed genes were screened between the calycosin-treated cells and control (524 genes upregulated and 328 genes downregulated). The pathway enrichment suggested that the role of calycosin in B-CPAP cells is closely related to apoptosis-related genes and p70S6 Kinase. Transmission electron microscopy found an increase in autophagosomes in calycosin-treated cells. Sestrin2 in human PTC tissues and B-CPAP cells was lower than in normal thyroid tissues and cells. And the pharmacological effects of calycosin in PTC cells were related to Sestrin2 activation, increased p-AMPK and inhibited p-mTOR and p-p70S6Kinase; these alterations were reversed when silencing Sestrin2. In conclusion, calycosin has an inhibitory eﬀect on PTC via promoting apoptosis and autophagy through the Sestrin2/AMPK/mTOR pathway.